Prevalence of Proteinuria in Dogs With Immune‐Mediated Disease - James C. Barton; Alexander J. German; Erin M. O'Connell (Journal of Veterinary Internal Medicine)
ABSTRACT Background Proteinuria is associated with autoimmune diseases in humans. There is minimal evidence in the veterinary literature on proteinuria and its association with immune‐mediated disease in dogs. Hypothesis Renal proteinuria is common in dogs with immune‐mediated disease. Dogs presenting with pyrexia or immune‐mediated polyarthritis (IMPA) are more likely to have proteinuria. Animals One hundred and forty‐four dogs with primary immune‐mediated diseases. Methods Retrospective, observational study. Data collected included signalment, travel outside the United Kingdom, duration of clinical signs, diagnosis, urinalysis, and urine protein–creatinine ratio (UPCR). Non‐proteinuric, mild proteinuria, moderate proteinuria, and severe proteinuria were defined as UPCR < 0.5; ≥ 0.5–1; ≥ 1–2; ≥ 2, respectively. Exclusion criteria included azotemia, hypoalbuminemia (< 2.0 g/dL), foreign travel, active urine sediment or positive culture, glucocorticoid therapy for greater than 24 h prior to presentation, or medication known to influence UPCR. Results Sixty‐seven dogs were non‐proteinuric (47%; 95% confidence interval [95% CI]: 38%, 55%), 25 mildly proteinuric (17%; 95% CI: 9%, 26%), 15 moderately proteinuric (10%; 95% CI: 2%, 19%), and 37 severely proteinuric (26%; 95% CI: 17%, 34%). On multiple logistic regression analysis, female dogs (odds ratio [OR]: 3.24; 95% CI: 1.49, 7.42), individuals with pyrexia (OR: 6.59; 95% CI: 3.00, 15.37), or hemoglobinuria (OR: 27.21; 95% CI: 4.79, 516.56) were more likely to have proteinuria. There was an association between steroid‐responsive meningitis‐arteritis and the magnitude of proteinuria on multiple linear regression (p = 0.025); this was not confirmed on multiple logistic regression. Conclusions and Clinical Importance Proteinuria is common in dogs with immune‐mediated disease and can be severe. Screening for proteinuria could be considered part of the diagnostic assessment for dogs with immune‐mediated disease.